Comparative evaluation of different histoprocessing methods - Singla, Kartesh; Sandhu, Simarpreet Virk; Pal, Rana A.G.K.; Bansal, Himanta; Bhullar, Ramanpreet Kaur; Kaur, Preetinder (International Journal of Health Sciences, 2017)
Objectives: Tissue processing for years is carried out by the conventional method, which is a time-consuming technique resulting in 1-day delay in diagnosis. However, in this area of modernization and managed care, rapid diagnosis is increasingly desirable to fulfill the needs of clinicians. The objective of the present study was to compare and determine the positive impact on turnaround times of different tissue processing methods by comparing the color intensity, cytoplasmic details, and nuclear details of the tissues processed by three methods. Methods: A total of sixty biopsied tissues were grossed and cut into three equal parts. One part was processed by conventional method, second by rapid manual, and third by microwave-assisted method. The slides obtained after processing were circulated among four observers for valuation. Sections processed by the three techniques were subjected to statistical analysis by Kruskal–Wallis test. Cronbach’s alpha reliability test was applied to assess the reliability among observers. One-way analysis of variance (ANOVA) was used for comparing mean shrinkage before and after processing. Results: All observers were assumed to be reliable as the Cronbach’s reliability test was statistically significant. The results were statistically non-significant as observed by Kruskal–Wallis test. One-way ANOVA revealed a significant value on comparison of the tissue shrinkage processed by the three techniques. The histological evaluation of the tissues revealed that the nuclear-cytoplasmic contrast was good in tissues processed by microwave, followed by conventional and rapid manual processing techniques. The color intensity of the tissues processed by microwave was crisper, and there was a good contrast between the hematoxylin and eosin-stained areas as compared to manual methods. Conclusion: The overall quality of tissues from all the three methods was similar. It was not feasible to distinguish between the three techniques by observing the tissue sections. Microwave-assisted tissue processing has reduced the time from sample reception to diagnosis, thus enabling the same-day processing and diagnosis.